Electron vacancy-level dependent hybrid photoionization of the F−@C60+ molecule: a novel effect. (16th February 2022) - Ali, Esam; O'Brien, Taylor; Dennis, Andrew; El-Amine Madjet, Mohamed; Manson, Steven T; Chakraborty, Himadri S
Abstract: Our previous studies (Shields et al 2020 J. Phys. B: At. Mol. Opt. Phys. 53 125101; Shields et al 2020 Euro. Phys. J. D 74 191) have predicted that the atom-fullerene hybrid photoionization properties for X = Cl, Br and I endohedrally confined in C60 are different before and after an electron transfers from C60 to the halogen. It was further found as a rule that the ionization dynamics is insensitive to the C60 level the electron originates from to produce X − @ C 60 + . In the current study, we report an exception to this rule in F@C60 . It is found that when the electron vacancy is situated in the C60 level that participates in the hybridization in F − @ C 60 +, the mixing becomes dramatically large leading to strong modifications in the photoionization of the hybrid levels. This novel effect is fundamentally based on a level-crossing phenomenon driven by the electron transfer in F@C60 . But when the vacancy is at any other pure level of C60, the level-invariance is retained showing weak hybridization. Even though this case of F@C60 is an exception in the halogen@C60 series, the phenomenon can be more general and can occur with compounds of other atoms caged in a variety of fullerenes. Possible experimental studies are suggested to benchmark the present results.